2020
DOI: 10.1016/j.geomorph.2020.107058
|View full text |Cite
|
Sign up to set email alerts
|

Understanding spatio-temporal barrier dynamics through the use of multiple shoreline proxies

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…Furthermore, Orford and Anthony (2011) observed that long-term (multi-annual to centennial) gravel barrier change is principally controlled by extreme events, sediment supply and sea level rise rate but that sediment supply can be discounted 'under conditions of limited longshore sediment supply (essentially swash-aligned, single beachridge barrier systems)' (Orford and Anthony, 2011, 43). Evidence of the BPBS displaying swash-aligned behaviour is provided by Pollard et al (2020) whose historical shoreline change analysis of the BPBS showed that the classic drift-aligned signal of downdrift westward barrier extension (evident from 1886 to 2016) was replaced in the period 1981-2016 by a shift towards a more swash-aligned system, characterised by no clear alongshore variation in the rate of shoreline change (see Fig. 3, (Pollard et al, 2020)).…”
Section: Numerical Model Chain Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Orford and Anthony (2011) observed that long-term (multi-annual to centennial) gravel barrier change is principally controlled by extreme events, sediment supply and sea level rise rate but that sediment supply can be discounted 'under conditions of limited longshore sediment supply (essentially swash-aligned, single beachridge barrier systems)' (Orford and Anthony, 2011, 43). Evidence of the BPBS displaying swash-aligned behaviour is provided by Pollard et al (2020) whose historical shoreline change analysis of the BPBS showed that the classic drift-aligned signal of downdrift westward barrier extension (evident from 1886 to 2016) was replaced in the period 1981-2016 by a shift towards a more swash-aligned system, characterised by no clear alongshore variation in the rate of shoreline change (see Fig. 3, (Pollard et al, 2020)).…”
Section: Numerical Model Chain Set-upmentioning
confidence: 99%
“…Evidence of the BPBS displaying swash-aligned behaviour is provided by Pollard et al (2020) whose historical shoreline change analysis of the BPBS showed that the classic drift-aligned signal of downdrift westward barrier extension (evident from 1886 to 2016) was replaced in the period 1981-2016 by a shift towards a more swash-aligned system, characterised by no clear alongshore variation in the rate of shoreline change (see Fig. 3, (Pollard et al, 2020)). We conclude, therefore, that our focus on cross-shore profile change is justified in the context of the contemporary behaviour of this barrier system.…”
Section: Numerical Model Chain Set-upmentioning
confidence: 99%
“…At several sites, this management becomes unsustainable into the future, raising the question as to what might happen if sediment management ceases and natural processes can return unchecked to these frontages. In the 1980s and 90s, a number of publications were dedicated to the natural ontogeny and in particular roll-back of coarse clastic barrier beaches focussing on barriers in Ireland [10][11][12] and Canada [13][14][15] followed from 2000 by publications on barriers like Hurst Spit [16], Porlock [17,18], Cley [19][20][21] and Sillon de Talbert [22][23][24], where previous management including sediment movement had ceased or hard structures been removed, or where new management was going to be introduced [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sites with higher spatio-temporal survey resolution have become available [21,43] and the present study is an extension of this early work at Medmerry. As such the paper addresses the following questions:…”
Section: Introductionmentioning
confidence: 99%
“…Further work by Plomaritis et al [17] developed this classification into a regional scale assessment of storm related overwash and barrier breaching using a numerical model of coastal overwash [18], allowing the formulation of overwash volumes without the need for numerical modeling which is computationally expensive over larger spatial scales. Recent literature has begun to study mixed sand-gravel beaches under different tectonic settings [19], and where gradients in both alongshore and cross-shore sediment transport play a role in governing the sediment transport regime [20][21][22].…”
mentioning
confidence: 99%